Aramid nanometer fiber / cellulose nanometer alkene composite thermoelectric thin film and preparation method and application thereof
By regulating the composite preparation method of cellulose and aramid nanofibers, the insufficient application of existing thermoelectric films in low-grade heat collection is solved, and the thermoelectric performance is improved and process simplified is achieved. It is suitable for wearable electronics and micro devices.
Patent Information
- Application Number
- CN202411590432.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-14
AI Technical Summary
Existing thermoelectric film materials have poor performance in low-grade heat collection, and the preparation process is complex and costly, and have failed to effectively coordinate the optimization of conductivity and Seebeck coefficient.
The preparation method of composite thermoelectric film of aramid nanofiber and cellulose nanoene is adopted. By controlling the sulfuric acid concentration, reaction temperature and time, the degree of graphitization of the outer molecular chain of cellulose is regulated, and the concentration and content of the aramid nanofiber dispersion is combined. , a composite film with excellent conductivity and thermoelectric properties was prepared.
It has achieved improvement in thermoelectric performance, coordinatedly improving the thermoelectric potential and conductivity of the composite film, solved the problem of thermoelectric parameter coupling, has good flexibility, mechanical properties and heat resistance, and is suitable for wearable electronics and micro devices.
Smart Images

Figure CN119306988A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of thermoelectric films, and in particular relates to an aramid nanofiber / cellulose nanoolefin composite thermoelectric film with high thermoelectric potential, and a preparation method and application thereof. Background Art
[0002] A large amount of heat is generated in households, nature, and industrial production processes, but most of the heat is directly dissipated into the environment as waste heat, of which low-grade waste heat (<100°C) accounts for more than 60%. Faced with increasingly severe environmental pollution problems and energy crises, the development of low-grade energy collection and conversion technologies is of great significance to promoting sustainable development. Thermoelectric materials have attracted much attention because they can realize the mutual conversion of thermal energy and electrical energy. Depending on the type of carriers, they can be divided into electronic thermoelectric materials and ionic thermoelectric materials. Although traditional semiconductor electronic thermoelectric materials exhibit excellent conductivity, their low Seebeck coefficient (~μV K -1 The problems of low-grade heat harvesting, high cost, high toxicity, lack of flexibility, and the fact that the operating temperature is usually not in the low-grade range, have severely limited its application in low-grade heat harvesting.
[0003] In contrast, ionic thermoelectric materials have mV K -1 The advantages of high Seebeck coefficient, mechanical flexibility, low thermal conductivity, and low cost show a wider application prospect in low-grade heat collection. The thermoelectric conversion efficiency of ionic thermoelectric materials is mainly measured by the thermoelectric figure of merit ZT. i To evaluate (ZT i =S i 2 σ i T / κ, where S i is the ionic Seebeck coefficient, σ i is the electrical conductivity, T is the temperature, and κ is the thermal conductivity). It can be seen that high S i , high σ i and low κ are the key to achieving excellent thermoelectric performance of ionic thermoelectric materials. At present, most studies mainly prepare organic / inorganic composite thermoelectric materials by combining polymer materials with inorganic materials to improve thermoelectric performance.
[0004] The invention patent application with publication number CN115274998A discloses a thermoelectric material, specifically a method for preparing a flexible Cu-Se nanowire / methyl cellulose composite thermoelectric film, comprising the following steps: dissolving SeO2 and β-cyclodextrin in water to obtain solution A; dissolving ascorbic acid in water to obtain solution B; dropping solution A into solution B, stirring and centrifuging, transferring the precipitate to anhydrous ethanol for ultrasonic dispersion and standing, and dispersing the product in ethylene glycol after centrifugation to obtain a dispersion; dissolving copper sulfate in ethylene glycol to obtain solution I; dissolving ascorbic acid in water to obtain solution II; adding solution I and solution II to the dispersion, centrifuging and drying to obtain a powder; dissolving MC in water and adding the powder to obtain a composite slurry; printing the composite slurry on a substrate by screen printing, and drying to obtain a crude product; cold pressing the crude product; annealing the cold pressed crude product to obtain a flexible composite thermoelectric film.
[0005] Publication number CN117915743A proposes dispersing PEDOT nanowires synthesized by the self-assembled micelle soft mold method in methanol, and preparing a PEDOT nanowire film by a vacuum filtration process; then TeO2 is dissolved in concentrated nitric acid to prepare an electrolyte, and a Bi2Te3 / PEDOT nanowire thermoelectric composite film is prepared by an electrochemical deposition process.
[0006] However, the method provided in the above patent application does not decouple the restraining relationship between conductivity and Seebeck coefficient, and fails to achieve the coordinated optimization of the two physical quantities. In addition, the preparation process is complicated, the experimental environment is demanding, and the cost is high, which further limits the feasibility of its industrial application. Therefore, how to synergistically improve thermoelectric potential and conductivity and prepare thermoelectric thin film materials with excellent performance is a problem that needs to be solved urgently. Summary of the invention
[0007] The invention provides a method for preparing an aramid nanofiber / cellulose nanoolefin composite thermoelectric film. The method can prepare a composite thermoelectric film with high thermoelectric performance and electrical conductivity.
[0008] The present invention provides a method for preparing an aramid nanofiber (ANF) / cellulose nanoolefin composite thermoelectric film, comprising:
[0009] S1. Add microcrystalline cellulose to a sulfuric acid solution, react at 70-90° C. for 2-6 hours under an inert gas atmosphere to obtain a suspension, wherein the mass / volume ratio of the microcrystalline cellulose to the sulfuric acid solution is 1 g: 50-100 mL, and the concentration of the sulfuric acid solution is 50-80 wt %. The suspension is centrifuged, washed with water, and freeze-dried to obtain a conductive cellulose nanoene;
[0010] S2, grinding the conductive cellulose nanoolefin, and then homogenizing it in an ice bath, then adding the aramid nanofiber dispersion, and continuously oscillating and ultrasonically dispersing for 0.5-2h to obtain a uniform and stable mixed solution, and finally vacuum filtering the mixed solution to obtain a composite film;
[0011] S3, soaking the composite film in an electrolyte mixture of polyvinyl alcohol and potassium chloride, and then vacuum drying to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film.
[0012] By synergistically regulating the concentration and amount of sulfuric acid added, as well as the reaction temperature and time, the degree of graphitization of the outer molecular chains of cellulose can be controlled so that the nanocellulose retains its morphology, size, hydrophilicity, and rich oxygen-containing functional groups while having excellent conductivity.
[0013] Preferably, in the mixed solution, the mass ratio of the conductive cellulose nanoolefin to the aramid nanofiber is 0.3-3: 1. The present invention controls the content of the conductive cellulose nanoolefin to obtain a composite film with good film quality and excellent thermoelectric performance.
[0014] Preferably, the concentration of the aramid nanofiber dispersion is 0.8-1.5 mg / mL.
[0015] Preferably, the method for preparing the aramid nanofiber dispersion comprises:
[0016] S21, adding aramid chopped fibers into a mixed solution of potassium hydroxide and dimethyl sulfoxide to perform a deprotonation reaction;
[0017] S22. Add the deprotonated mixed solution dropwise into water, stir for 4-6 hours in an ice bath to obtain a re-protonated suspension, filter the re-protonated suspension, wash with water, and disperse it in water again, and homogenize it in an ice bath to obtain an aramid nanofiber dispersion as a supporting skeleton for the composite film.
[0018] Preferably, the length of the aramid chopped fibers is 0.5-1.0 cm, and the aramid chopped fibers are para-aramid fibers.
[0019] Preferably, the solid-to-liquid ratio of the aramid chopped fibers, potassium hydroxide, and dimethyl sulfoxide is 0.5-1.5 g: 1-1.5 g: 100 mL.
[0020] Preferably, the deprotonation reaction time is 5-7 days.
[0021] The invention controls the length and content of aramid short fibers to make them undergo sufficient chemical cracking and deprotonation reaction in a dimethyl sulfoxide / potassium hydroxide system, thereby realizing nano-fiberization of macro fibers and obtaining a uniform and stable aramid nanofiber mixed solution.
[0022] Preferably, in the electrolyte mixture, the solid-liquid ratio of the polyvinyl alcohol, potassium chloride and water is 1 g: 1-2.5 g: 10 mL.
[0023] On the other hand, the present invention further provides an aramid nanofiber / cellulose nanoolefin composite thermoelectric film, wherein the aramid nanofiber / cellulose nanoolefin composite thermoelectric film is prepared by the aramid nanofiber / cellulose nanoolefin composite thermoelectric film preparation method.
[0024] On the other hand, the present invention also provides the application of the aramid nanofiber / cellulose nanoolefin composite thermoelectric film in wearable electronics or micro devices. The aramid nanofiber / cellulose nanoolefin composite thermoelectric film prepared by the present invention exhibits excellent ion conductivity and thermoelectric performance, which can effectively solve the current problem of serious thermoelectric parameter coupling. It also has the advantages of good flexibility, superior mechanical properties, high heat resistance, etc., which greatly improves its processability and practicality, and has good application prospects in the fields of wearable electronics or micro devices.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] According to the Boltzmann distribution, there is a large difference in the concentration of anions and cations in the double layer. Therefore, introducing a temperature gradient into the ANF with charged nanochannels can couple the difference in thermophoretic mobility and improve the sensitivity of the thermoelectric response. At the same time, cellulose nanoene enhances the conductivity of the composite membrane, synergistically improves the thermoelectric potential and conductivity of the composite membrane, and achieves a thermoelectric figure of merit ZT i improvement. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a digital photo of the aramid nanofiber / cellulose nanoolefin composite thermoelectric film prepared in Example 1;
[0028] Figure 2 is an IV curve diagram of the aramid nanofiber / cellulose nanoolefin composite thermoelectric film prepared in Example 1;
[0029] Figure 3 is the conductivity diagram of the aramid nanofiber / cellulose nanoolefin composite thermoelectric film prepared in Example 1;
[0030] Figure 4 It is the transmission electron microscope image of the cellulose nanoene prepared in Example 5 and the corresponding selected area electron diffraction (SAED) image. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments.
[0032] Example 1
[0033] 1) 1 g of potassium hydroxide was dissolved in 100 mL of dimethyl sulfoxide, and 1 g of chopped aramid fiber (1 cm) was added, and mechanical stirring was performed at room temperature. After reacting for 7 days, a dark red mixture was obtained;
[0034] 2) slowly dropping the mixture obtained in step 1 into water, stirring and reacting in an ice bath for 4 hours, filtering and washing the obtained suspension after the reaction, and then redispersing it in water, and homogenizing it in an ice bath to obtain an aramid nanofiber dispersion with a concentration of 1 mg / mL;
[0035] 3) adding 1 g of microcrystalline cellulose to 80 mL of 64 wt % sulfuric acid solution, stirring and reacting in a 90° C. water bath under a nitrogen atmosphere for 4 hours, and after the reaction, centrifuging and washing the obtained suspension with water, and freeze-drying to obtain conductive cellulose nanoene;
[0036] 4) 30 mg of the conductive cellulose nanoene was ground and then homogenized in an ice bath, then added to 10 ml of aramid nanofiber dispersion, ultrasonically dispersed for 30 minutes, and a composite film was prepared by vacuum filtration;
[0037] 5) Add 1g of polyvinyl alcohol and 1g of potassium hydroxide to 10ml of water, stir at 80°C until a uniform mixture is obtained, cool to room temperature, place the composite film obtained in step 4 into the mixture to fully soak it, and vacuum dry it at room temperature to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film.
[0038] Example 2
[0039] 1) 1 g of potassium hydroxide was dissolved in 100 mL of dimethyl sulfoxide, and 1 g of chopped aramid fiber (0.5 cm) was added, and mechanical stirring was performed at room temperature. After reacting for 5 days, a dark red mixture was obtained;
[0040] 2) slowly dropping the mixture obtained in step 1 into water, stirring and reacting in an ice bath for 4 hours, filtering and washing the obtained suspension after the reaction, and then redispersing it in water, and homogenizing it in an ice bath to obtain an aramid nanofiber dispersion with a concentration of 1 mg / mL;
[0041] 3) adding 1 g of microcrystalline cellulose to 80 mL of 64 wt % sulfuric acid solution, stirring and reacting in a 90° C. water bath under a nitrogen atmosphere for 4 hours, and after the reaction, centrifuging and washing the obtained suspension with water, and freeze-drying to obtain conductive cellulose nanoene;
[0042] 4) grinding 20 mg of the conductive cellulose nanoene, and then homogenizing it in an ice bath, and then adding it to 20 ml of the aramid nanofiber dispersion, ultrasonically dispersing it for 30 minutes, and preparing a composite film by vacuum filtration;
[0043] 5) Add 1g polyvinyl alcohol and 1.25g potassium hydroxide to 10ml water, stir at 80°C until a uniform mixture is obtained, cool to room temperature, place the composite film obtained in step 4 into the mixture to fully soak it, and vacuum dry it at room temperature to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film.
[0044] Example 3
[0045] 1) 1.2 g of potassium hydroxide was dissolved in 100 mL of dimethyl sulfoxide, and 1.2 g of short-cut aramid fiber (0.5 cm) was added, and mechanical stirring was performed at room temperature. After reacting for 6 days, a dark red mixture was obtained;
[0046] 2) slowly dropping the mixture obtained in step 1 into water, stirring and reacting in an ice bath for 4 hours, filtering and washing the obtained suspension after the reaction, and then redispersing it in water, and homogenizing it in an ice bath to obtain an aramid nanofiber dispersion with a concentration of 1.2 mg / mL;
[0047] 3) adding 1 g of microcrystalline cellulose to 80 mL of 64 wt % sulfuric acid solution, stirring and reacting in a 90° C. water bath under a nitrogen atmosphere for 4 hours, and after the reaction, centrifuging and washing the obtained suspension with water, and freeze-drying to obtain conductive cellulose nanoene;
[0048] 4) 10 mg of the conductive cellulose nanoene was ground and then homogenized in an ice bath, then added to 20 ml of aramid nanofiber dispersion, ultrasonically dispersed for 30 minutes, and a composite film was prepared by vacuum filtration;
[0049] 5) Add 1g of polyvinyl alcohol and 1.5g of potassium hydroxide to 10ml of water, stir at 80°C until a uniform mixture is obtained, cool to room temperature, put the composite film obtained in step 4 into the mixture to fully soak, and dry in vacuum at room temperature to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film, such as Figure 1 shown.
[0050] Example 4
[0051] 1) 1.5 g potassium hydroxide was dissolved in 100 mL dimethyl sulfoxide, and 1 g short-cut aramid fiber (1 cm) was added, and mechanical stirring was performed at room temperature. After reacting for 5 days, a dark red mixture was obtained;
[0052] 2) slowly dropping the mixture obtained in step 1 into water, stirring and reacting in an ice bath for 4 hours, filtering and washing the obtained suspension after the reaction, and then redispersing it in water, and homogenizing it in an ice bath to obtain an aramid nanofiber dispersion with a concentration of 1 mg / mL;
[0053] 3) adding 1 g of microcrystalline cellulose to 80 mL of 64 wt % sulfuric acid solution, stirring and reacting in a 90° C. water bath under a nitrogen atmosphere for 4 hours, and after the reaction, centrifuging and washing the obtained suspension with water, and freeze-drying to obtain conductive cellulose nanoene;
[0054] 4) 10 mg of the conductive cellulose nanoene was ground and then homogenized in an ice bath, then added to 30 ml of aramid nanofiber dispersion, ultrasonically dispersed for 30 minutes, and a composite film was prepared by vacuum filtration;
[0055] 5) Add 1g polyvinyl alcohol and 2g potassium hydroxide to 10ml water, stir at 80°C until a uniform mixture is obtained, cool to room temperature, put the composite film obtained in step 4 into the mixture to fully soak it, and vacuum dry it at room temperature to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film.
[0056] Example 5
[0057] 1) 1 g of potassium hydroxide was dissolved in 100 mL of dimethyl sulfoxide, and 1 g of chopped aramid fiber (1 cm) was added, and mechanical stirring was performed at room temperature. After reacting for 7 days, a dark red mixture was obtained;
[0058] 2) slowly dropping the mixture obtained in step 1 into water, stirring and reacting in an ice bath for 4 hours, filtering and washing the obtained suspension after the reaction, and then redispersing it in water, and homogenizing it in an ice bath to obtain an aramid nanofiber dispersion with a concentration of 1 mg / mL;
[0059] 3) adding 1 g of microcrystalline cellulose to 100 mL of 64 wt % sulfuric acid solution, stirring and reacting in a water bath at 80° C. under a nitrogen atmosphere for 4 hours, and after the reaction, centrifuging and washing the obtained suspension with water, and freeze-drying to obtain conductive cellulose nanoene;
[0060] 4) 30 mg of the conductive cellulose nanoene was ground and then homogenized in an ice bath, then added to 10 ml of aramid nanofiber dispersion, ultrasonically dispersed for 30 minutes, and a composite film was prepared by vacuum filtration;
[0061] 5) Add 1g of polyvinyl alcohol and 1g of potassium hydroxide to 10ml of water, stir at 80°C until a uniform mixture is obtained, cool to room temperature, place the composite film obtained in step 4 into the mixture to fully soak it, and vacuum dry it at room temperature to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film.
[0062] like Figure 4 From the transmission electron microscopy and SAED images of the conductive cellulose nanoene prepared in Example 5, it can be seen that the H + The dehydration and carbonization of cellulose molecular segments by ions form a graphitized nanostructure, which gives it excellent conductivity. At the same time, the size effect and chemical property advantages of the retained nanocellulose are conducive to its combination with aramid nanofibers to prepare high-quality composite films.
[0063] Performance Analysis:
[0064] like Figure 2 As shown, ions exhibit linear Ohmic behavior during transmembrane transport, indicating that the composite membrane has a symmetrical structure.
[0065] like Figure 3 As shown in Figure 2, the conductivity measurement reveals the charge-controlled ion transport process in the composite membrane. In the high concentration region, the ion conductivity follows the volume rule and is linear; when the concentration is <10mM, the conductivity deviates from the volume value and gradually approaches the platform; in the low concentration region, the thickness of the double layer increases and is comparable to the channel size. Since the ANF surface carries a negative charge, the oppositely charged cation (K + ) will be enriched in the channel, while anions with the same charge (Cl - ) will be excluded, forming a closed unipolar environment, which is conducive to enhancing the thermophoretic mobility difference.
Claims
1. A method for preparing an aramid nanofiber / cellulose nanoolefin composite thermoelectric film, characterized in that: include: S1. Add microcrystalline cellulose to a sulfuric acid solution, react at 70-90° C. for 2-6 hours under an inert gas atmosphere to obtain a suspension, wherein the mass / volume ratio of the microcrystalline cellulose to the sulfuric acid solution is 1 g: 50-100 mL, and the concentration of the sulfuric acid solution is 50-80 wt %. The suspension is centrifuged, washed with water, and freeze-dried to obtain a conductive cellulose nanoene; S2, grinding the conductive cellulose nanoolefin, and then homogenizing it in an ice bath, then adding the aramid nanofiber dispersion, and continuously oscillating and ultrasonically dispersing for 0.5-2h to obtain a uniform and stable mixed solution, and finally vacuum filtering the mixed solution to obtain a composite film; S3, soaking the composite film in an electrolyte mixture of polyvinyl alcohol and potassium chloride, and then vacuum drying to obtain an aramid nanofiber / cellulose nanoolefin composite thermoelectric film.
2. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 1, characterized in that: In the mixed solution, the mass ratio of the conductive cellulose nanoene to the aramid nanofiber is 0.3-3:
1.
3. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 1, characterized in that: The concentration of the aramid nanofiber dispersion is 0.8-1.5 mg / mL.
4. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 1, characterized in that: The method for preparing the aramid nanofiber dispersion comprises: S21, adding aramid chopped fibers into a mixed solution of potassium hydroxide and dimethyl sulfoxide to perform a deprotonation reaction; S22. Add the deprotonated mixed solution dropwise into water, stir for 4-6 hours in an ice bath to obtain a re-protonated suspension, filter the re-protonated suspension, wash with water, disperse it in water again, and homogenize it in an ice bath to obtain an aramid nanofiber dispersion.
5. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 4, characterized in that: The length of the aramid chopped fibers is 0.5-1.0 cm, and the aramid chopped fibers are para-aramid fibers.
6. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 4, characterized in that: The solid-to-liquid ratio of the aramid chopped fibers, potassium hydroxide and dimethyl sulfoxide is 0.5-1.5 g: 1-1.5 g: 100 mL.
7. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 4, characterized in that: The deprotonation reaction time is 5-7 days.
8. The method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 1, characterized in that: In the electrolyte mixture, the solid-liquid ratio of the polyvinyl alcohol, potassium chloride and water is 1g:1-2.5g:10mL.
9. An aramid nanofiber / cellulose nanoolefin composite thermoelectric film, characterized in that: The aramid nanofiber / cellulose nanoolefin composite thermoelectric film is prepared by the method for preparing the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to any one of claims 1 to 8.
10. Use of the aramid nanofiber / cellulose nanoolefin composite thermoelectric film according to claim 9 in wearable electronics or micro devices.
Citation Information
Patent Citations
Preparation method of flexible Cu-Se nanowire / methyl cellulose composite thermoelectric thin film
CN115274998A
Preparation method of flexible Bi2Te3 / PEDOT nanowire thermoelectric composite film
CN117915743A